PENGELOLAAN SUMBERDAYA PERIKANAN BERBASIS MASYARAKAT (PSPBM) MELALUI MODEL CO-MANAGEMENT PERIKANAN - A. Muluk Alains; Seprianti Eka Putri; Prilia Haliawan (Muhammadiyah University Press, 2009)
This study aims to identify the Co-Management PSPBM, on review of socio-economic dynamics and conflict management of traditional fishermen, in the city of Bengkulu. The nature of this study used qualitative methods-phenomenalogis with research sites in the city of Bengkulu. Data collection techniques include collecting secondary data and primary data through the determination of the informants, observation, depth interviews, FGDs. Results of research found a patron-client relationships are still very dominating this region, and once the economy of social security for fishermen. Kinship relations are generally good. Social solidarity is still high but not a guarantee, and survival strategies of fishermen are still relatively traditional sort because only starting point on the sea fishing only and does not extend to other areas that still use of marine resources. Results of analysis of conflict in general can be seen conflict among fishermen that happened in the three study sites are: class conflict, or vertical conflict and agrarian conflict.